Sistem Informasi Pendaftaran Siswa Baru Menggunakan Extreme Programming - Reflan Nuari (Journal of Data Science and Information Systems, 2023)
The new student registration information system is a digital platform designed to simplify and increase the efficiency of the student registration process at an educational institution. This study aims to create a new student registration system that can facilitate the registration process and data collection of new students using an extreme programming approach. The test results show that the application of the new student registration system that has been made shows results of 100% in accordance with the functions needed by the school.